The perfectionism principle in the representation of corporate achievements (based on the annual reports’ material of industrial companies) - Yu. A. Filyasova (Управление)
The article considers the verbal representation elements of perfectionism in annual reports. The study is intended to analyze the perfectionist principle as an integral annual reports’ characteristic of companies with high rating positions. The material for the research consisted of 2.882 contextual uses of keywords with the superlative semantics – “best”, “maximum”, “high”, as well as those with the meaning of progressive development – “increase”, “improvement”, “upgrading”, “growth”, which reflect the semantics of the concept “perfectionism” and characterize the companies’ own activity. The research was conducted with the following methods: continuous sampling in the reports’ documents on the listed keywords, semantic selection, quantitative analysis, contextual analysis, semantic classification, data comparison. On average the coefficient of the presence of perfectionism elements in the volume of annual reports varies from 0.66 to 2.15. The data obtained can be considered high, given that many report pages contain numerical and illustrative data. Among the studied contextual uses, the most frequent were words with broader semantics: “increase”, “high”, “best”, “increase”, which can be used both from the standpoint of performance and from the point of view of the process of performing production activities. The usage of the keywords has a systemic character as it embraces all types of companies’ activities: the increase of the ecological and corporate social responsibility levels; business process improvement; product quality enhancement; the board of directors’ activity improvement, the increase in profits and company value, and some others. The perfectionism principle is oriented to maintaining long-term relationships with external and internal categories of users by ensuring that the performance of activities meets the expectations of interested groups of users.